Descent groups, chiefdoms, and South African historiography - Hammond-Tooke, W. D. (My University, 1984)
A number of impressive historical studies by a group of young South African scholars has recently appeared, seeking to apply new insights in tracing the effects of the imposition of colonial rule over the indigenous peoples of the sub-continent (e.g. Slater 1976; Hedges 1978; Peires 1981; Bonner 1980, 1983; Guy 1979, 1981; Delius 1982, Hamilton and Wright 1984). Some of these authors, notably Slater, Hedges, Guy, Bonner, Hamilton and Wright, seek, as a starting point of their analyses, to establish the nature of the ‘mutation’ to chieftainship that must have occurred from a previous period in which there were no chiefs. These works focus mainly on the Nguni, especially the incorporative states of Zulu and Swazi; others, like those of Peires on the Xhosa and Delius on the Pedi, tend to assume chieftainship as given and take their analyses from there.
African Studies Seminar series. Paper presented July, 1984